Estudo da produção de biodiesel utilizando etanol e óleo de soja ou de macaúba, catalisada por lipase de mamona e de Thermomyces lanuginosus - Silva, Felipe de Almeida (2015)
Biodiesel, a fuel produced from renewable sources, is a sustainable substitute to meet the growing global energy demand. The transesterification (alcoholysis) of oils and fats is the route most used in biodiesel synthesis, resulting in high yields in a reduced reaction period. An alternative route for the synthesis of biodiesel is the hydroesterification process that consists of the hydrolysis of vegetable oil (triglyceride), purification of the formed free fatty acids (FFA), followed by esterification with ethanol, resulting in high quality products and co-products. This dissertation aimed to study the synthesis of biodiesel by transesterification and hydroesterification of soybean and macaw palm kern oils with ethanol, catalyzed by lipase of dormant seeds of castor bean crude extract (CBCE) in solvent-free media. It was studied and defined as the best protocol for preparing CBCE the incubation in acetone 4 °C for 4 hours with no subsequent washings with acetone. The CBCE showed a high catalytic activity of the enzyme extract in hydrolysis reactions in acid medium (pH 4.5). However, no activities were bserved in esterification and transesterification reactions, possibly due to the low stability in the presence of organic solvents and alcohols. The CBCE showed low stability at temperatures higher than ambient temperatures. The complete conversion of soybean oil in the hydrolysis was reached after 6 h of reaction, in the absence of salt, 37 °C, 1,000 rpm, 4% w/v CBCE. Under the same conditions, it reached up to 90% conversion of macaw palm oil. Subsequently, the kinetic study of soybean oil hydrolysis catalyzed by CBCE was carried, studying the influence of the catalyst and substrate concentration on the initial rates of the reaction; and temperature influence throughout the reaction. Using 1% w/v CBCE, the highest initial reaction rate was obtained for the oil concentration of 147 mM (128.2 g/L oil). For higher substrate concentrations, a decrease of reaction speed was observed, indicating a decrease in enzyme activity under these conditions. The kinetic model of Michaelis-Menten with the substrate inhibition adequately fitted the experimental data (R² = 0.96). The estimated values for the kinetic parameters were: Vmax (2.85 ± 0.75 mM / min), KM (182.95 ± 65.80 mM) and KI (217.23 ± 95.34 mM). These results reveal a promising application of CBCE as robust biocatalyst in the hydrolysis of oils for the production of concentrated FFA. Since CBCE does not catalyze esterification reaction, the FFA obtained in the hydrolysis were purified and used for the synthesis of ethyl esters in solvent-free media, using the lipase of Thermomyces lanuginosus (TLL) covalently immobilized in epoxy resin as biocatalyst. The maximum ester conversion reached (85%) was obtained after 2 hours of reaction when soybean FFA was used as substrate; and 71% for macaw palm FFA after 6 hours of reaction. The low thermal stability of the CBCE motivated the castor bean lipase purification, aiming subsequent enzyme immobilization. Immobilization allows reuse of enzymes and an increase in its stability, depending on the strategy used. The lipase extraction assays at different pHs showed a maximum selectivity for the 50 mM sodium citrate buffer, pH 4.0 and a maximum yield for the 50 mM sodium phosphate buffer, pH 7.0. Adsorption experiments on hydrophobic and ionic supports were performed. Preliminary results showed that the castor bean lipase was strongly adsorbed on supports activated with amino groups (83%), where hydrolytic activity was observed both in derivatives as well in the supernatants containing the desorbed lipase.